1930
DOI: 10.1113/jphysiol.1930.sp002644
|View full text |Cite
|
Sign up to set email alerts
|

Studies on diffusion through surviving isolated intestine

Abstract: THE process of absorption of soluble substances from the intestine has generally been investigated by determining either the amount of substance which disappears in a given time after placing the solution in an isolated or T hiry Vella loop in the living animal, or its concentration in the absorbing fluid. On account of the obvious difficulties, both experimental and chemical, standing in the way of successful application of the latter method, when the blood of the portal vein is used, we have sought for some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1930
1930
2002
2002

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…PREVIOUS work on the absorption of sugars has shown that the rate of transference of glucose from solutions placed in the lumen of surviving segments of intestine into the outer saline environment is at a maximum at 0*75M concentration [Auchinachie, Macleod and Magee, 1930;Macleod, Magee and Purves, 1930]. In order to investigate the full significance of this optimal concentration it was considered desirable to test its applicability to the living animal.…”
mentioning
confidence: 99%
“…PREVIOUS work on the absorption of sugars has shown that the rate of transference of glucose from solutions placed in the lumen of surviving segments of intestine into the outer saline environment is at a maximum at 0*75M concentration [Auchinachie, Macleod and Magee, 1930;Macleod, Magee and Purves, 1930]. In order to investigate the full significance of this optimal concentration it was considered desirable to test its applicability to the living animal.…”
mentioning
confidence: 99%
“…WE have shown [Auchinachie, Macleod and Magee, 1930] that certain solutes pass from the lumen of surviving segments of mammalian intestine into the outer nutrient fluid at body temperature in a manner indicating some degree of persistence of selective action in the intestinal wall, located probably in the epithelial cells [Magee, 1930]. We have also demonstrated that there is an optimal concentration of glucose, 3M/4, at which diffusion occurs most rapidly under these conditions.…”
mentioning
confidence: 72%
“…In the experiments of the present series our technique as previously described [Auchinachie, Macleod and Magee, 1930] has been modified so as to prevent any appreciable fall in temperature of the segments during their removal from the animal. The abdomen was opened in a warm bath of Tyrode, the intestine washed out gently with warm normal saline and segments of equal length measured, excised and fastened on the tubes while still submerged.…”
mentioning
confidence: 99%
“…We have therefore concluded that no loss of sugar by bacterial action in the loops is to be expected under our conditions. Although the large intestine in the living animal was almost impermeable to glucose, when it was filled with glucose solution and suspended in a bath of warm Ringer solution, according to the method of Auchinachie, Macleod & Magee [1930], a certain amount of glucose passed through into the surrounding fluid.…”
Section: Methodsmentioning
confidence: 99%